A atividade de leitura de histórias em quadrinhos/tiras na formação do leitor crítico: um estudo no programa Ação Cidadã - Claudino, Valentina Imaculada (2008)
This study is inserted in the Reading in Different Areas Project (LDA), developed by the Acting as Citizen Research Program (PAC PUC/SP) and aims to investigate the teaching-learning process of reading, through the work carried out with comic books (HQ)/ strips text genre, based on proceedings adopted in the LDA Project. It also intends to discuss possible transformations that might have occurred along the reading activity in the classroom. This research is inserted in the Applied Linguistics field and was developed during Portuguese Language lessons with 6th grade students Primary School children - enrolled in a state school. The study was based on the Socio- Historical-Cultural Activity Theory (Vygotsky, 1934/2003, 1934/1999, 1978/1998, 1982/1999; Leontiev, 1977, 1978 & Engeström, 1999). The discussions addressed the reading concepts and critical reading (Kleiman, 1998, 2006; Rojo, 2003, 2006; Lerner, 2006; Chartier, 1998, 2001), genre (Bakhtin, 1929/2006; Bronckart, 1999 & Schneuwly, 1999, 2004) and also the contributions of comic books (HQ)/ strips genre for the learning process in the school contexts. It was developed as a critical action-research in a collaborative perspective (Kincheloe, 1997; Magalhães, 1994, 2006, 2008 & Alarcão, 2003), which aims to promote critical thinking about one´s own action, and collaboratively promote transformations in practices. For data analysis, the context of production and thematic content through lexical choices (Bronckart, 1999, 2006) were used. The results indicated that the lessons based on didactic units served as basis for the occurrence of changes. The readers began to explor their action, discursive and linguistic capacities (Dolz & Schneuwly, 1998) throughout their reading learning processes, indicating a critical and deepened approach reading comprehension. Another observed transformation was related to collaboration and interaction in the activity that was dedicated to the sharing of senses in order to collaboratively produce meanings